Digital Business Communication Study: The Use of E-Wallets on the TikTok Shop E-Commerce Platform as a Digital Financial Transaction Solution for @fdperfume - Anggrayni , Dewi; Rahmiyanti, Sev; Sugih, Agung Permana; Sahat, Febrisal (Al-Infaq: Jurnal Ekonomi Islam, 2025)
Business communication is closely associated with interactions conducted by business actors with the aim of facilitating business transactions. Nowadays, companies have increasingly utilized digital media as a means of communication and business transactions through social media. However, business transaction failures often occur due to fraud employing various schemes. This study aims to explore how TikTokShop entrepreneurs optimize digital communication in financial transactions through e-wallets, as exemplified by @fdperfume Halal. Through interviews with the owner of the TikTokShop account @fdperfume Halal, it was found that e-wallets offer practical solutions that replace cash transactions and cumbersome bank transfers. The speed of payment notifications and transaction time efficiency are major advantages, while promotions such as cashback effectively attract customer interest and increase sales volume. This study identifies three main sub-themes for each indicator: first, digital financial transactions, including efficiency and cashback; second, the safety of digital transactions, encompassing security and cybercrime; and third, user trust in e-commerce, consisting of loyalty and credibility. Although there are concerns regarding the risks of cybercrime, business actors feel that e-wallet service providers have made efforts to minimize these risks. Overall, e-wallets have significant potential to evolve as a modern, practical, and secure digital payment solution by continually improving security, innovative features, and attractive promotional programs within the e-commerce ecosystem, particularly on TikTokShop.